Radiation toxicity in prostate cancer patients - Stanić, Jelena; Stankovic, Vesna; Nikitovic, Marina (Medicinski podmladak, 2021)
Abstract Prostate cancer (PC) is the most frequent male tumor, accounting for about one-third of all cancers in men. Because survival is often favorable regardless of therapy, treatment decisions may depend on therapy-specific health outcomes. The majority of men initially diagnosed with localized PC ultimately die with, rather than of, their disease. As a result, men who are diagnosed will live many years with the treatment’s sequelae. The major therapeutic strategies include radical prostatectomy or external beam radiotherapy. Radiotherapy is one of the curative treatment options. The tumor dose-response relationship has been studied and is widely accepted. The unsatisfactory local control with doses <70Gy led to dose escalation using highly precise radiotherapy techniques - three-dimensional conformal radiotherapy and intensity-modulated radiotherapy enabling the delivery of high radiation doses up to 74-78 Gy. Bowel, rectal and urinary toxicities are the principal limiting factors in delivering a high dose. Acute symptoms include a change in bowel habits, urgency, and fecal incontinence. The most commonly reported late toxicities were chronic diarrhea, proctitis, or rectal bleeding. Several factors have been associated with increased gastrointestinal toxicity such as larger bowel volume receiving high doses, the patient’s age, diabetes, and concomitant use of androgen deprivation therapy. Bladder damage resulting from acute radiation toxicity is manifested as radiation cystitis (frequent urination and dysuric disorders). Smoking, previous abdominopelvic surgeries, and the use of diuretics significantly affect the occurrence of acute genitourinary toxicity grade ≥ 2. Risk factors for the development of late genitourinary complications are higher radiation dose, previous urinary problems, transurethral interventions, and acute genitourinary complications. It is essential to strike a balance between the therapeutic benefits and radiotherapy side effects. Severe late complications significantly reduce the quality of life (QOL) of PC survivors. Early detection and proper evaluation of complications are especially important in increasing the patient’s QOL.